Molecular signatures of hemagglutinin stem-directed heterosubtypic human neutralizing antibodies against influenza A viruses. - Yuval Avnir; Aimee S Tallarico; Quan Zhu; Andrew S Bennett; Gene Connelly; Jared Sheehan; Jianhua Sui; Amr Fahmy; Chiung-yu Huang; Greg Cadwell; Laurie A Bankston; Andrew T McGuire; et al. (PLoS Pathogens, 2014)
Recent studies have shown high usage of the IGHV1-69 germline immunoglobulin gene for influenza hemagglutinin stem-directed broadly-neutralizing antibodies (HV1-69-sBnAbs). Here we show that a major structural solution for these HV1-69-sBnAbs is achieved through a critical triad comprising two CDR-H2 loop anchor residues (a hydrophobic residue at position 53 (Ile or Met) and Phe54), and CDR-H3-Tyr at positions 98±1; together with distinctive V-segment CDR amino acid substitutions that occur in positions sparse in AID/polymerase-η recognition motifs. A semi-synthetic IGHV1-69 phage-display library screen designed to investigate AID/polη restrictions resulted in the isolation of HV1-69-sBnAbs that featured a distinctive Ile52Ser mutation in the CDR-H2 loop, a universal CDR-H3 Tyr at position 98 or 99, and required as little as two additional substitutions for heterosubtypic neutralizing activity. The functional importance of the Ile52Ser mutation was confirmed by mutagenesis and by BCR studies. Structural modeling suggests that substitution of a small amino acid at position 52 (or 52a) facilitates the insertion of CDR-H2 Phe54 and CDR-H3-Tyr into adjacent pockets on the stem. These results support the concept that activation and expansion of a defined subset of IGHV1-69-encoded B cells to produce potent HV1-69-sBnAbs does not necessarily require a heavily diversified V-segment acquired through recycling/reentry into the germinal center; rather, the incorporation of distinctive amino acid substitutions by Phase 2 long-patch error-prone repair of AID-induced mutations or by random non-AID SHM events may be sufficient. We propose that these routes of B cell maturation should be further investigated and exploited as a pathway for HV1-69-sBnAb elicitation by vaccination.